Transhumanismus als Symptom symbolischer Verelendung: zur anthropologischen Herausforderung der Digitalen Revolution - Hoff, Johannes (Transhumanismus, 2020)
Transhumanism as a Symptom of Symbolic Misery. The Anthropological Challenge of the Digital Revolution. This essay provides a concise reappraisal of the philosophical discussion on technology of the last 30 years in the light of the technologically induced political and cultural crisis of our present time. It starts with a philosophical assessment of popular discussions on transhuman ism and interprets the more backwards-oriented mindset of this movement as a symptom of the cultural decline of liberalism. After a short genealogy of this decline, it concludes with an outline of the real anthropological challenges of the digital revolution and its implications for the Christian image of man.